ENHANCEMENT OF DYE DEGRADATION ACTIVITY BY MICROORGANISMS – A REVIEW - A. SHANMUGAPRIYA,; SULOCHANA SOMASUNDARAM, (International Journal of Pharma and Bio Sciences, 2016)
A variety of synthetic dyestuffs released by the textile industry pose a threat to environmental safety. Existing effluent treatment procedures are unable to remove these dyestuffs completely from effluents because of their colour fastness, stability and resistance to degradation. Microbial processes for the treatment of textile wastewater have the advantage of being cost-effective, environmental friendly and producing less sludge. The most promising microorganisms for wastewater treatment are those isolated from sites contaminated with dyes or from the sludge of treatment plants because they have adapted to survive in adverse conditions. The mechanism of microbial decolourisation occurs from adsorption, enzymatic degradation or a combination of both. The enzymes like reductases and oxidases are involved in the microbial degradation process. The goal of microbial treatment is to decolourise and detoxify the dye-contaminated effluents. This paper provides a detailed review on the enhancement of dye degradation activity by microorganisms.